Flap Monitoring: What We Know and What Is To Come - Yalçın, Can Ege (Cerrahpaşa Medical Journal, 2025)
Microsurgical free tissue transfer is a cornerstone of modern reconstructive surgery, offering high success rates in restoring complex defects. However, free flap failure, though infrequent, remains a serious complication associated with increased morbidity, prolonged hospitalization, and limited secondary reconstructive options. Early detection of vascular compromise is critical to maximizing flap salvage potential. Consequently, flap monitoring has become an essential component of postoperative care. This review provides a comprehensive overview of current methods used in free flap monitoring, with a focus on their clinical utility, advantages, limitations, and evidence base. Noninvasive techniques—including clinical examination, handheld Doppler, temperature assessment, infrared thermography, near-infrared spectroscopy, laser Doppler flowmetry, and smartphone-integrated tools—are widely used due to their simplicity and ease of application. In contrast, invasive methods such as implantable Doppler probes, indocyanine green angiography, microdialysis, and biochemical or bioimpedance-based sensors offer more direct or sensitive measures of perfusion but often involve higher cost, technical expertise, or limited accessibility. Despite ongoing technological advancements, clinical monitoring remains the gold standard due to its reliability, accessibility, and cost-effectiveness. Nevertheless, adjunctive tools can improve diagnostic accuracy, particularly in buried flaps or ambiguous cases. A tailored, multimodal approach—balancing invasiveness, accuracy, and feasibility—may optimize outcomes in free flap surgery Cite this article as: Yalçın E. Flap monitoring: what we know and what is to come. Cerrahpaşa Med J 2025, 49, 0045, doi: 10.5152/cjm.2025.25045